Constitutive modeling of viscoplasticity including phase transformations for graded thermo‐mechanical processing. Issue 1 (14th December 2021) - Westermann, Hendrik; Reitz, Alexander; Mahnken, Rolf; Grydin, Olexandr; Schaper, Mirko
Abstract: Tailored materials are of particular interest in modern engineering applications due to their potentially high strength and residual ductility. During hot forming processes, such as press hardening, microstructure transformations in low carbon steels are considered to achieve the production of tailored components. The relevant microstructure mechanisms during thermo‐mechanical processing are visco‐plastic deformation and phase transformations. Thus, we present an extension to an existing thermodynamically consistent continuum mechanical model. The evolution of phase transformations under inhomogeneous temperature loading in a homogeneous tensile specimen are illustrated.